Insights into the nucleation role of cellulose crystals during crystallization of poly(β-hydroxybutyrate). (10th December 2015) - Chen, Jianxiang; Xu, Chunjiang; Wu, Defeng; Pan, Keren; Qian, Aiwen; Sha, Yulu; Wang, Li; Tong, Wei
Highlights: Cellulose crystals act as the nucleation agent during PHB crystallization. Nucleating effect dominates the overall kinetics of PHB crystallization. Nucleation ability difference between MCC and NCC is temperature-sensitive. PHB and its composites show similar morphological evolution with temperature. Composites have smaller band space with degraded ring-banded structure. Abstract: Cellulose crystals, including microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC), were used as the fillers to prepare green composites with poly( β -hydroxybutyrate) (PHB) by melt mixing for crystallization study. The results reveal that the spherulite morphology of PHB and its composites depends highly on the crystallization temperature, evolving from bundle shaped to ring-banded and finally to irregular or zigzag textures with increase of temperature. However, the ring-banded structure is strongly affected by the presence of cellulose crystals, and the average band space decreases evidently with the addition of MCC or NCC. Compared with PHB/MCC composite, PHB/NCC composite shows degraded spherulite structure with smaller band space and higher flocculation level of peak-to-valley height because of stronger unbalanced stresses in this system. Besides, cellulose crystals can act as good heterogeneous nucleating agent to accelerate the crystallization of PHB, which is further confirmed by the polarized optical microscopy observations and the kinetic analyses.